Creating Animation as Audiovisual Media Learning to Improve Motivation and Social Subject Outcome of 5th grade of Elementary School at SD Negeri 067245 Medan Selayang - Risa Damira; Daulat Saragi; Naeklan Simbolon (RIRAI Publisher, 2023)
This research aims to determine the feasibility, practicality and effectiveness of audiovisual media in the form of animation for class IV students at SD Negeri 067245 Medan Selayang. The research model used is research and development (R&D) using Thiagarajan's 4D design. The research subjects were 54 material and media expert validators, teachers and class IV students, each consisting of 27 students in the experimental class and 27 students in the control class. Based on research findings, validation results by material experts were 87%, media experts 88% and were included in the valid (feasible) category. Furthermore, the practicality results obtained from the teacher questionnaire results were 87.5% in the